Cost-effectiveness of a novel, non-active implantable device as a treatment for refractory gastro-esophageal reflux disease. (31st December 2023) - Harper, Sam; Grodzicki, Lukasz; Mealing, Stuart; Gemmill, Liz; Goldsmith, Paul J.; Ahmed, Ahmed R.
Abstract: Aims: Gastro-esophageal reflux disease (GERD) is a common, chronic gastrointestinal condition characterized by heartburn, chest pain, regurgitation, and bloating. The current standard of care includes chronic treatment with proton pump inhibitors (PPIs) or, in selected patients, laparoscopic anti-reflux surgery. RefluxStop is a novel implantable device indicated for GERD patients eligible for laparoscopic surgical treatment. The aim of this analysis was to assess the cost-effectiveness of RefluxStop against available treatment options for GERD. Material and methods: A Markov model was developed to assess the cost-effectiveness of RefluxStop compared with PPI-based medical management (MM) and two surgical management options, LNF and magnetic sphincter augmentation (MSA, LINX system), in people with GERD. Clinical outcomes and costs were estimated over a lifetime horizon from the UK National Health Service perspective and an annual discount rate of 3.5% was applied. Results: RefluxStop showed favorable surgical outcomes compared with both LNF and MSA. The base case incremental cost-effectiveness ratios compared with MM, LNF, and MSA were £4, 156, £6, 517, and £249 per QALY gained, respectively. At the UK cost-effectiveness threshold of £20, 000 per QALY gained, the probability that RefluxStop was cost-effective against MM, LNF, and MSA was 100%, 93%, and 100%, respectively. Limitations: The model presented the results of a comparison, with evidence for RefluxStop derived from its single-arm CE mark trial and that for comparators from the literature. The varied clinical care pathway of individual GERD patients was necessarily simplified for modeling purposes, and necessary assumptions were made; however, the model results proved robust to sensitivity analyses. Conclusions: Introduction of RefluxStop was estimated to extend life expectancy and improve quality-of-life of GERD patients when compared with MM, LNF, and MSA. The results of the cost-effectiveness analysis demonstrated that RefluxStop is highly likely to be a cost-effective treatment option within NHS England.